Sequential selective supercritical fluid extraction (S3FE) of triglycerides and flavonolignans from milk thistle (Silybum marianum L, Gaertn) - C. Palaric; S. Atwi-Ghaddar; Q. Gros; C. Hano; E. Lesellier (Journal of CO2 Utilization, 2023)
Supercritical fluid extraction with carbon dioxide is nowadays one of the best approaches on an economic and ecological point of view for the extraction of natural compounds from plants. Besides, many seeds or fruits contain both lipids, as triglycerides, which can be used for food or cosmetic industries, and polyphenols which do have many bioprotective effects for the human health. By using successively pure carbon dioxide and carbon dioxide added with a polar modifier, either pure ethanol or a ethanol/water mixture, we achieved first the extraction of triglycerides of the milk thistle seeds, followed by the extraction of the flavonolignans, which are bioactive compounds. Effects of pressure (15 and 25 MPa) and temperature (40 and 60 °C) were studied on the lipids extraction efficiency. For flavonolignans, the polar compounds, the impact of modifier amount (pure ethanol from 10% to 40%) and water percentage in ethanol (5–15%) were compared. The duration of the two sequential steps to achieve the complete seed defatting and to increase the flavonolignan recovery were also studied. The complete lipids extraction was achieved with pure CO2 at 40 °C, 25 MPa for 30 min whereas the extraction of flavonolignans was achieved with 20% of modifier (wate/ethanol 15/85) during 90 min. The analysis of the triglyceride composition of milk thistle seed were studied by using supercritical fluid chromatography (SFC), whereas the analysis of flavonolignans was carried out by an improved Ultra-high-pressure liquid chromatography (UHPLC) method.